From patriarchy to gender justice: Qur’anic foundations and transformations in Islamic family law - Khairul Umami; Mega Puspita (Institute for Research and Community Service, Universitas Islam Negeri Kiai Haji Achmad Siddiq Jember, East Java, Indonesia., 2023)
Gender equality in Islam remains a central concern in contemporary Islamic family law scholarship, particularly regarding women’s reproductive roles, inheritance law, and the provisions of ʿiddah and iḥdād, which are frequently perceived as sources of injustice toward women. While previous studies have explored these issues through hermeneutical, Islamic feminist, and social constructionist perspectives, most have examined them in isolation and have not sufficiently addressed their interrelationship as components of a unified process of family law transformation rooted in Qur’anic values. This study analyzes the concept of gender equality from a Qur’anic perspective and examines the transformation of Islamic family law as a means of advancing gender justice. A qualitative library research design is employed, using the thematic exegesis method (tafsīr mawḍūʿī) alongside qualitative content analysis. Data sources include the Qur’an, hadith, classical and contemporary Qur’anic commentaries, and scholarly literature on gender and Islamic family law. The findings indicate that the Qur’an establishes gender equality on three foundational principles: piety, shared human origin, and human dignity. These principles are reflected in family law reforms through the transformation of women’s reproductive roles, the recognition of women’s economic rights within inheritance law, and the establishment of social protection mechanisms through the provisions of ʿiddah and iḥdād. The study develops a conceptual framework that situates these three dimensions as interconnected mechanisms of Islamic family-law transformation from patriarchal traditions toward gender justice grounded in Qur’anic values. The findings support a contextual and maqāṣid al-sharīʿah-oriented approach to Islamic family law that promotes justice, public welfare, and respect for human dignity in contemporary Muslim societies.